Kuroneko = The black cat inside the bamboo grove - Hayashi, Hikaru 1931-2012 (Eureka, 2013)
"[...] In this magnificently eerie and romantic film a mother and daughter-in-law are raped and murdered by pillagers, but return from the dead as vampiric cat spirits intent on revenge. As the ghosts lure soldiers into the bamboo groves, a fearless samurai, Gintoki, is sent to stop their reign of terror. [...]" [cover]
Bildformat 2.35:1 original aspect ratio 1080p HD transfer
Orig.: Japan 1968
Enth. Original theatrical trailer ; optional English subtitles ; 32-Page booklet with an essay by Doug Cummings ; a 1972 interview with Shindô conducted by Joan Mellen ; and rare archival imagery